Just Take My Heart - Clark, Mary Higgins; Maxwell, Jan (New York Audioworks, 2009)
When Broadway star Natalie Raines is murdered after discovering who killed her former roommate, it sets off a chain of events that puts many lives in danger, including assistant prosecutor Emily Wallace.
Abridged.
Compact discs.
Read by Jan Maxwell.
Keywords: Heart -- Fiction -- Transplantation; Murder -- Fiction -- Investigation; Audiobooks; Cape Cod Bay (Mass.) -- Fiction; Mystery fiction; Suspense fiction